Enhancing Students' Critical Thinking in Algebra through STEAM-Based Flood Simulation and Mitigation Projects - Alfirda, Egidia; Agnita Siska Pramasdyahsari; Rina Dwi Setyawati; Dahal, Niroj (RANGE: Jurnal Pendidikan Matematika, 2025)
Flooding is a recurring environmental issue in various regions of Indonesia, posing significant threats to both the natural environment and community welfare. At the same time, Indonesian students continue to show low performance in international assessments such as TIMSS and PISA, particularly in critical thinking and problem-solving competencies. These dual challenges highlight the urgent need for innovative educational approaches that not only address academic deficiencies but also connect students to real-world problems. In response to this, the study explores the integration of Science, Technology, Engineering, Arts, and Mathematics (STEAM) within a Project-Based Learning (PjBL) framework—specifically applied to algebra content related to flood mitigation. The research employed an experimental design with a quantitative approach, involving control and experimental student groups to examine the impact of the STEAM-based intervention on critical thinking skills. Results indicated that students in the experimental group significantly outperformed those in the control group in post-test scores. These findings suggest that STEAM mitigation project-based learning is effective in enhancing students' critical thinking abilities. It not only prepares learners to tackle complex, real-world issues but also underscores the importance of contextual and innovative pedagogy in 21st-century education. The implication is clear: adopting contextualized, interdisciplinary learning models can be a strategic solution to enhance educational quality and improve student readiness in addressing global and local challenges.